SELF-EFFICACY, PAIN INTENSITY, AND EARLY MOBILIZATION ABILITY AMONG POST-OPERATION PATIENTS IN A PRIVAT HOSPITAL - Lasmini Lasmini; Dewi Murti Sari; Rusnoto Rusnoto; Muhamad Jauhar ((IJP) Indonesia Jurnal Perawat, 2024)
Fractures are a serious health problem that threatens public health. Every year, there is an increasing trend in fracture cases in each region. Injuries, including traffic accidents, cause fracture cases, falls from high places, and bone fragility factors. If not treated properly, the impact of a fracture is symptoms such as deformity, loss of sensation (numbness, possibly due to nerve damage/bleeding), abnormal movement, swelling, and pain. To know the correlation of self-efficacy and pain intensity with early mobilization ability in post-ORIF surgery patients at PKU Muhammadiyah Pamotan Hospital. The type of research used correlational analysis with a cross-sectional approach. This research was conducted at PKU Muhammadiyah Pamotan Hospital in August 2023-September 2023. The sample size was 34 respondents with a total sampling technique. The instruments used were a General self-efficacy (GSE) self-efficacy questionnaire, a Numerical Rating Scale (NRS) pain intensity assessment, and an early mobilization ability questionnaire in post-ORIF surgery patients. The data analysis used Spearman Rho statistics. The study showed a good relationship between self-efficacy (p=0.000) and pain intensity (p=0.000) with the ability to mobilize post-ORIF surgery patients at PKU Muhammadiyah Pamotan Hospital early. Self-efficacy and pain intensity influence post-op patients' early mobilization ability. Nurses need to increase the patient's self-confidence to carry out early mobilization and provide pain management to minimize the causes of the patient's inability to mobilize early, which is related to the pain complaints they feel.